Comparative Effects of Intragastric and Intraduodenal Administration of Quinine on the Plasma Glucose Response to a Mixed-Nutrient Drink in Healthy Men: Relations with Glucoregulatory Hormones and Gastric Emptying. Issue 6 (10th March 2021) - Rose, Braden D; Bitarafan, Vida; Rezaie, Peyman; Fitzgerald, Penelope C E; Horowitz, Michael; Feinle-Bisset, Christine
ABSTRACT: Background: In preclinical studies, bitter compounds, including quinine, stimulate secretion of glucoregulatory hormones [e.g., glucagon-like peptide-1 (GLP-1)] and slow gastric emptying, both key determinants of postprandial glycemia. A greater density of bitter-taste receptors has been reported in the duodenum than the stomach. Thus, intraduodenal (ID) delivery may be more effective in stimulating GI functions to lower postprandial glucose. Objective: We compared effects of intragastric (IG) and ID quinine [as quinine hydrochloride (QHCl)] administration on the plasma glucose response to a mixed-nutrient drink and relations with gastric emptying, plasma C-peptide (reflecting insulin secretion), and GLP-1. Methods: Fourteen healthy men [mean ± SD age: 25 ± 3 y; BMI (in kg/m 2 ): 22.5 ± 0.5] received, on 4 separate occasions, in double-blind, randomly assigned order, 600 mg QHCl or control, IG or ID, 60 min (IG conditions) or 30 min (IG conditions) before a mixed-nutrient drink. Plasma glucose (primary outcome) and hormones were measured before, and for 2 h following, the drink. Gastric emptying of the drink was measured using a 13 C-acetate breath test. Data were analyzed using repeated-measures 2-way ANOVAs (factors: treatment and route of administration) to evaluate effects of QHCl alone and 3-way ANOVAs (factors: treatment, route-of-administration, and time) for responses to the drink. Results: After QHCl alone, there were effects of treatment, but not route of administration, on C-peptide, GLP-1, and glucose ( P  < 0.05); QHCl stimulated C-peptide and GLP-1 and lowered glucose concentrations (IG control: 4.5 ± 0.1; IG-QHCl: 3.9 ± 0.1; ID-control: 4.6 ± 0.1; ID-QHCl: 4.2 ± 0.1 mmol/L) compared with control. Postdrink, there were treatment × time interactions for glucose, C-peptide, and gastric emptying, and a treatment effect for GLP-1 (all P  < 0.05), but no route-of-administration effects. QHCl stimulated C-peptide and GLP-1, slowed gastric emptying, and reduced glucose (IG control: 7.2 ± 0.3; IG-QHCl: 6.2 ± 0.3; ID-control: 7.2 ± 0.3; ID-QHCl: 6.4 ± 0.4 mmol/L)  compared with control. Conclusions: In healthy men, IG and ID quinine administration similarly lowered plasma glucose, increased plasma insulin and GLP-1, and slowed gastric emptying. These findings have potential implications for lowering blood glucose in type 2 diabetes. This study was registered as a clinical trial with the Australian New Zealand Clinical Trials at www.anzctr.org.au as ACTRN12619001269123.